Implementing the Functions of Village Consultancy Boards in Government Implementation in Pattongko Village, Sinjai Central District - Syamsiah Hasyim; Sri Rahayu Juniati; Andi Bahrun Syam (International Journal of Management Science, 2023)
This study aimed to determine the implementation of the functions of the Village Consultative Body in the administration of government in Pattongko Village and the factors that supported and hindered it. This research was qualitative descriptive to provide a clear picture and description as a whole with guaranteed truth of the existing problems regarding the implementation of the functions of the Village Consultative Body in the administration of government in Pattongko Village. Data was collected through observation, interviews, and documentation. The results showed that the Functions of the Village Consultative Body in the Implementation of Government in Pattongko Village, Sinjai Tengah District, were the implementation of the Badan Permusyawaratan Desa (BPD) function in discussing and agreeing on the Draft Village Regulation and monitoring the performance of the Village Head had been going well. However, there were still weaknesses in accommodating and channeling village aspirations that still need to be maximized because hamlets still need to be visited to accommodate and channel aspirations from the community.